The age and genomic integrity of neurons after cortical stroke in humans - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; Racz, Attila; Tatarishvili, Jemal; Lindgren, Emma; Csonka, Tamas; Csiba, Laszlo; Hortobagyi, Tibor; Mehes, Gabor; Englund, Elisabet; Solnestam, Beata Werne; et al. (Nature Neuroscience, 2014)
It has been unclear whether ischemic stroke induces neurogenesis or neuronal DNA rearrangements in the human neocortex. Using immunohistochemistry; transcriptome, genome and ploidy analyses; and determination of nuclear bomb test-derived (14)C concentration in neuronal DNA, we found neither to be the case. A large proportion of cortical neurons displayed DNA fragmentation and DNA repair a short time after stroke, whereas neurons at chronic stages after stroke showed DNA integrity, demonstrating the relevance of an intact genome for survival.
EVALuna2:22305